The role of influencers and opinion formers marketing on creative brand communication - Černikovaitė, Miglė Eleonora; Karazijienė, Žaneta (Creativity Studies, 2023)
The growing power of social media and the fast change of communication forms encourages marketers to explore new ways for brands to communicate creatively and effectively. The aim of this study is to determine how to reveal the involvement of influencers in creative forms of brand communication by analysing (comparatively) the expression of Lithuanian and foreign influencers in social networks. Research methodology and results: analysis academic literature and quantitative content analysis in social networks. Literature analysis reviled, that the main dimensions of communication strategy with influencers involves four stages: setting the objectives of the campaign; setting the criteria to find out right influencer; setting campaign duration and platform; influencer performance analysis. The results of the study showed that one of the most important and most inclusive step is choosing the right influencer. It is important to choose not only based on brand profile, but also to evaluate the potential risks when working with one or another influencer. Brands are recommended to choose those influencers that are not overloaded with another brands,integrate advertising into video format and reveal that their integration is brand advertising, because consumers tend to choose the products or services which are chosen by the celebrities they follow.